Validity of Learning Material About Particle Dynamics Contained Quranic Verses Using Direct Instruction Model - Marlina; Mastuang; Dewantara, Dewi (Proceeding International Conference on Science and Engineering, 2021)
Abstract. The use of learning materials contained Quranic verses in physics subject will contribute to train and optimizing problem solving skills to students. This article aims to describe the validation of learning materials of particel dynamics contained Quranic verses using direct instruction teaching model. The development research used ADDIE model with learning materials as the subject of the research and validity data and suggestions for improvement by 3 academics and 2 practitioners. Validation is one of the processes at the part of the development stage. The validity of learning materials is measured using a validation sheet dan then determined based on validation by expert which are stated or invalid. If valid, it will be categorized again as very high, high, enough, low, and very low. The conclusion of this article is learning materials contained Quranic verses using direct instruction teaching model is valid and categorized as very high. Based on data analysis, it can be concluded that learning materials are eligible to be used in learning process.